2019
DOI: 10.1186/s12875-019-1027-3
|View full text |Cite
|
Sign up to set email alerts
|

Accepting new patients who require opioids into family practice: results from the MAAP-NS census survey study

Abstract: Background: Acceptance to a family practice is key to access and continuity of care. While Canadian patients increasingly report not being able to acquire acceptance to a family practice, little is known about the association between requiring opioids and acceptance. We aim to determine the proportion of family physicians who would accept new patients who require opioids and describe physician and practice characteristics associated with willingness to accept these patients. Methods: Census telephone survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Our findings among OAT recipients align with recently published studies employing surveys and qualitative analyses. In a Canadian survey of 354 family physicians accepting new patients, nearly one-third would not accept patients who required opioids [15], and participants in 2 qualitative studies among people with an OUD cited challenges securing ongoing primary care, perceived as being associated with stigma relating to their SUD [9,11]. The effect of stigma on barriers to primary care access may also be evident in our study, as nearly 90% of OAT recipients had their physician end their initial primary care enrolment compared to approximately 80% among chronic pain patients and opioid-unexposed individuals.…”
Section: Plos Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…Our findings among OAT recipients align with recently published studies employing surveys and qualitative analyses. In a Canadian survey of 354 family physicians accepting new patients, nearly one-third would not accept patients who required opioids [15], and participants in 2 qualitative studies among people with an OUD cited challenges securing ongoing primary care, perceived as being associated with stigma relating to their SUD [9,11]. The effect of stigma on barriers to primary care access may also be evident in our study, as nearly 90% of OAT recipients had their physician end their initial primary care enrolment compared to approximately 80% among chronic pain patients and opioid-unexposed individuals.…”
Section: Plos Medicinementioning
confidence: 99%
“…Therefore, we are unable to determine whether their patterns of primary care access differ from those receiving treatment for OUD. However, based on the literature regarding negative physician perceptions of people who use drugs [9,11,15], we anticipate that the findings among OAT recipients would be similar for those with OUD who are not actively receiving treatment. Fourth, we cannot confirm whether patients who lost their PCP were actively looking for another provider over the follow-up period.…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Patients may also have differential capacity to pursue attachment and may face discrimination in that process (Marshall et al, 2019). Hence, first-come-first-served centralized waitlists may be an insufficient approach that has the potential to be unfair and result in inequitable care and reattachment along socio-demographic axes.…”
Section: Discussionmentioning
confidence: 99%
“…The unintended consequence of this finding is that it may become difficult for some patients who need legitimate opioid prescriptions to find a family physician to prescribe for them. A recent survey in Nova Scotia showed that 28% of family physicians accepting new patients would not accept a new patient if the person is on opioids [ 11 ].…”
Section: Discussionmentioning
confidence: 99%